Teaching adolescents with disabilities : accessing the general education curriculum - 4 0 16; Deshler, Donald D.,;Schumaker, Jean B.; 5 (Thousand Oaks, California : Corwin Press, 2006)
Presents teachers and administrators with detailed, practical, research-validated practices for teaching adolescents with disabilities.
Includes bibliographical references and index.
Professional.
Keywords: 2 -- 0; 6; Education (Secondary);Education. -- Teenagers with disabilities;Handicapped -- United States.;United States; 20; 2